Clinical Course and Treatment of Patients with Atrophic Rhinitis After Covid-19 (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
To improve the efficiency of diagnostics and complex treatment of atrophic rhinitis in patients who have had COVID-19. Material and methods of the study: we observed 40 sick children aged 3 to 18 years with atrophic rhinitis who had had COVID-19 for the period from 2020 to 2023. The comparison group consisted of 20 sick children aged 3 to 18 years with atrophic rhinitis without COVID-19. Clinical and anamnestic research methods, general ENT examination, laboratory tests, saccharin test.